A comparative study between Fractional-N PLL and Flying-Adder PLL - Liming Xiu; Chen-Wei Huang; Ping Gui (2010 IEEE International Symposium on Circuits and Systems (ISCAS), 2010)
Frequency synthesis is one of the most important and most actively researched subjects in the field of VLSI mixed-signal circuit design. Among the existing techniques in this area, Fractional-N architecture is a widely used one for generating frequencies which are not integer multiple of the input reference frequency. Flying-Adder architecture is an emerging technique which is based on a new concept, Time-Average-Frequency, to generate frequencies. This paper presents an in-depth analysis and comparison between the two methods.